Changes in von Willebrand factor-cleaving protease (ADAMTS-13) in patients with aortic stenosis undergoing valve replacement or balloon valvuloplasty - Bander, Jeffrey; Elmariah, Sammy; Aledort, Louis M.; Dlott, Jeffrey; Stelzer, Paul; Halperin, Jonathan L.; Kini, Annapoorna S.; Sharma, Samin K. (Thrombosis and Haemostasis, 2012)
It was the objective of this study to determine whether reduced cleavage of von Willebrand factor (VWF) multimers following aortic valve replacement (AVR) is a consequence of reduced shear stress or postoperative changes in VWF cleavage protease (ADAMTS-13) activity. Aortic stenosis (AS) may be complicated by acquired von Willebrand disease. Aortic valve replacement (AVR) corrects the associated haematologic abnormalities. We enrolled 114 patients with severe AS scheduled for either balloon aortic valvuloplasty (BAV; n=64) or AVR (n=50). Haematologic assessments of VWF levels and activity and ADAMTS-13 were performed before and 24 hours after valve intervention. The VWF:RCo to VWF:Ag ratio, a surrogate for large VWF multimer activity, increased by 37% (p < 0.0001) after AVR and by 10% (p = 0.0002) after BAV. ADAMTS-13 activity significantly decreased after AVR (579 ± 127 to 468 ± 135 ng/ml; p<0.0001), but not after BAV (484 ± 153 to 529 ± 185 ng/ml; p = 0.10). By multivariable analysis, the change in VWF:RCo ratio after AVR was more strongly associated with the fall in ADAMTS-13 than with reduction of valve gradient; whereas the change in gradient better predicted the rise in VWF:RCo after BAV. In conclusion, both BAV and AVR reverse the haematological abnormalities of the acquired von Willebrand syndrome of AS and ADAMTS-13 levels decrease after AVR. These findings suggest that a portion of the haematologic benefit of AVR may be due to a postoperative decline in ADAMTS-13 rather than solely to relief of AS as previously thought.
Keywords: Acquired coagulation disorders; ADAMTS-13; aortic valve stenosis; balloon aortic valvuloplasty; von Willebrand factor